BOOK REVIEW Defining Moments: When Managers Must Choose Between Right and Right Joseph L Badaracco, Jr. Harvard Business Press - Barnes, PhD, John Arthur (ABAC ODI JOURNAL Vision. Action. Outcome, 2017)
The reviewers’ interest in this topic derived from teaching Tourism Business Ethics in the Tourism MBA Program. This book differs from many in my collection in that it involves three case studies in the more diverse business environment beyond tourism and hospitality. Each case discussed involves a higher level of complexity in finding both ethical philosophical and situational answers within the wider business community. The author Joseph L Badaracco Jr. is the John L Shad Professor of Business Ethics at Harvard University